Deformation and cooling history of the Central Qiangtang terrane, Tibetan Plateau and its tectonic implications. Issue 15 (13th October 2021) - Bi, Wenjun; Han, Zhongpeng; Li, Yalin; Li, Chengming; Wang, Chengshan; Zhang, Jiawei; Han, Jianyun; He, Haiyang; Qian, Xinyu; Xu, Tiankun; Ma, Zining
ABSTRACT: The Qiangtang terrane preserves an important record of the growth of the Tibetan Plateau since the Mesozoic; however, its deformation and cooling history remain poorly understood. To unravel this issue, we conducted geological mapping in the Esima area and detrital apatite fission track and (U–Th)/He analyses of the Esima–Rongtang region in the east segment of Central Qiangtang terrane. Our results indicate that the east segment underwent two stages of structural deformation and rapid cooling during 120–110 Ma and 55–38 Ma. By combining our results with those of previous studies of the deformation and cooling history in the west segment, we reconstructed the early spatial and temporal geological evolution of the Central Qiangtang terrane since the Late Jurassic–Early Cretaceous. The structural deformation and cooling of the west segment at 150–130 Ma was related to northward flat subduction of the Bangong–Nujiang oceanic slab. The structural deformation and cooling of the east segment at 120–110 Ma and the west segment at 110–70 Ma was controlled by oblique convergence between Lhasa and Qiangtang terranes. The structural deformation and cooling of the west and east segments at 55–38 Ma was associated with northward intracontinental subduction beneath the Qiangtang terrane induced by the Indo–Asian collision.